Does it pay for new firms to be green? An empirical analysis of when and how different greening strategies affect the performance of new firms. (1st October 2021) - Neumann, Thomas
Abstract: Despite the significant attention devoted to the impact of corporate greening strategies on firm performance, research has so far focused on established firms, leaving the situation in new firms unclear. In this study, it is hypothesised that the impact of greening strategies on the performance of new firms depends on the type of strategy, and that the firm's age positively moderates this impact. Using a cross-sectoral dataset of 11, 039 new firms from 36 countries, binary and ordinal logistic regressions were estimated for different start-up phases. The results indicate that new firms benefit from substantive greening strategies but, contrary to expectations, not from symbolic greening strategies. The performance of new firms in their later start-up phases was even found to be harmed if they adopt symbolic strategies but do not reinforce them with substantive actions (green-washing). No impact, or only a weakly positive impact was found for firms adopting both substantive and symbolic greening strategies (green-highlighting) or only substantive ones (brown-washing). Furthermore, the interaction analyses did not reveal any moderating effects of firm age, but additional investigation shows that the impacts of greening strategies do differ between age groups. Finally, robustness tests reveal that the relationship between substantive greening strategies and the performance of new firms is not linear but decreases with increasing environmental efforts. Highlights: Substantive greening strategies pay off for new firms aged up to 10 years. This positive link is not linear but weakens with higher environmental efforts. Symbolic greening and brown-washing are not related to the performance of new firms. Green-washing may backfire for firms in their later start-up phases. The impact of greening strategies differs between groups of different firm age.